2007
DOI: 10.1111/j.1937-5956.2007.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranked Items Auctions and Online Advertisement

Abstract: We study auctions for a set of commonly‐ranked items where each buyer has unit demand. This setting has promising applications in areas such as keyword auctions in the search engine advertising industry, the sale of quality‐ranked raw materials, etc. An auction mechanism suitable for this setting is the simultaneous pooled auction (SPA), where each bidder simultaneously submits a single bid and is allocated an object based on the rank of his bid among all the bids. We study how to improve the seller's expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The remaining three papers focus on three different issues in forward auctions that include: ranked items (Feng et al 2007), collusive behavior (Sosic 2007), and impatient bidders (Kwasnica and Katok 2007). Feng et al (2007) and Sosic (2007) use analytical models whereas Kwasnica and Katok (2007) use a simulation study. (2007) Caplice (2007) academic survey of bidders' behavior in forward auctions and suggest the following topics for further investigation: (1) the impact of customers' entry time in the auction process, (2) evaluation of the assumptions about the distribution of customers' valuations, (3) the impact of the number of units offered in each round of bidding, (4) transparency of the information to the bidders in multiple auctions, and (5) the effect of customers' learning phenomenon in multiple auctions.…”
Section: Forward Auctionsmentioning
confidence: 99%
“…The remaining three papers focus on three different issues in forward auctions that include: ranked items (Feng et al 2007), collusive behavior (Sosic 2007), and impatient bidders (Kwasnica and Katok 2007). Feng et al (2007) and Sosic (2007) use analytical models whereas Kwasnica and Katok (2007) use a simulation study. (2007) Caplice (2007) academic survey of bidders' behavior in forward auctions and suggest the following topics for further investigation: (1) the impact of customers' entry time in the auction process, (2) evaluation of the assumptions about the distribution of customers' valuations, (3) the impact of the number of units offered in each round of bidding, (4) transparency of the information to the bidders in multiple auctions, and (5) the effect of customers' learning phenomenon in multiple auctions.…”
Section: Forward Auctionsmentioning
confidence: 99%
“…The problem of dynamic pricing of Web contents was studied where revenue was generated from the subscription fees and advertisements (Kumar and Sethi, ). The auction model to determine the priorities of listing in searching results was presented to examine the firm's optimal bidding strategy (Lim and Tang, ; Feng et al , ).…”
Section: Operations Research Applications In Different Service Industmentioning
confidence: 99%
“…GSP is attractive to search engines because it helps to maximize profit. In addition, Feng et al [9] developed a simultaneous pooled auction (SPA) mechanism and showed that using reserve price in SPA significantly increased a search engine's revenue.…”
Section: Advertising Allocation Mechanismsmentioning
confidence: 99%